Extruded aquatic feed : impact of ingredients and processing on physical quality of feed, animal performance and environmental footprint - Graff, Tucker M (My University, 2025)
This dissertation presents a comprehensive investigation into the sustainability of extruded aquafeeds, focusing on the interplay between raw ingredient selection, physical feed characteristics, and extrusion processing parameters. The research specifically addresses the efficiency of production, physical quality, nutritional performance, and environmental footprint of feeds designed for key aquaculture species: Nile tilapia, Pacific white shrimp, and rainbow trout. A core objective was to evaluate grain sorghum and its derivatives as sustainable alternatives to conventional ingredients such as wheat and fishmeal. The studies explored the impact of various factors, including ingredient particle size, thermal and mechanical energy inputs during extrusion and drying, and the use of different cereal grain types and compositions. The primary aim was to identify optimal processing conditions that not only maximize pellet quality, feed digestibility, and animal growth performance but also minimize production costs and environmental impacts. Through an integrated approach combining processing trials, in vivo growth and digestibility assessments, detailed energy balance analyses, and cradle-to-gate life cycle assessments, this research provides a holistic understanding of how feed formulation and manufacturing choices influence the entire aquafeed production chain. Key findings demonstrate that grain sorghum is a viable alternative to wheat in aquafeeds, maintaining pellet quality and producing comparable animal performance while offering environmental benefits. Mechanical energy during processing of tilapia feeds for sorghum-based formulations ranged from 267.6 to 358.8 kJ/kg and 290.5 to 351 kJ/kg for wheat-based diets, with more intense particle size reduction increasing mechanical energy. For shrimp feeds, reducing the amount of preconditioning for both wheat and steam based diets resulted in higher mechanical energy inputs (228-260.4, and 237-288 kJ/kg, respectively). For sorghum-based diets specifically, it was found that gelatinization of feed was primarily affected by preconditioning inputs, with higher steam input leading to a greater degree of gelatinization (83-90.5%), while wheat-based feeds had similar gelatinization across all inputs (95-98%). For both wheat and sorghum-based diets for trout, processing under similar conditions resulted in similar bulk density numbers (372 and 382 g/L), floating percentage (~100%), pellet durability (86 and 87%), and water stability (~91%). Growth studies for sorghum-based feeds resulted in feed conversion ratios of 1.03-1.1, 1.44-1.51, and 0.96 for tilapia, shrimp, and trout. For wheat, these values were 1.11-1.13, 1.46-1.52, and 0.86 for tilapia, shrimp and trout. For all species except rainbow trout, sorghum-based diets exhibited improved feed conversion ratios. The research also highlighted that the choice of cereal grain significantly influences the environmental footprint, with sorghum-based feeds generally exhibiting lower environmental burdens. Net global warming potential values (kg CO2 eq/ton of animal growth) for sorghum and wheat-based diets were, respectively, 90.18 and 120.8 (trout feed), 160.4-224.4 and 240.79-303.52 (tilapia feeds), and 185.4-188.8 and 243.7-263.12 (shrimp feeds). It was found that while the main driver of global warming potential came from the choice of cereal grain used, total emissions were also drive by processing choices, with more intense processing such as increased particle size reduction (tilapia) and more intense preconditioning (shrimp) resulting in a larger environmental footprint. Furthermore, the inclusion of sorghum distillers dried grains (sDDGs) presents a sustainable protein source, though its environmental impacts necessitate careful formulation and processing to mitigate increased burdens from upstream agricultural activities. Ultimately, this dissertation provides evidence supporting the development of cost-effective, high-quality, and environmentally responsible aquafeeds that effectively utilize drought-tolerant, lower-input grains like sorghum. This contributes significantly to enhancing the resilience and sustainability of the global aquaculture industry, addressing challenges posed by rising ingredient costs and the increasing demand for sustainable ingredient sources.
Keywords: Extrusion; Aquaculture; Feed processing; Sorghum; Sustainability